MENINGKATKAN AKURASI FREE THROW SHOOTING BOLA BASKET MELALUI LATIHAN BERBASIS KONSENTRASI : STUDI KUASI-EKSPERIMEN - Dega Wasnawang; Dwi Cahyo Kartiko; Abdul Rachman Syam Tuasikal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Free throw is one of the fundamental skills that plays a crucial role in determining success in basketball games. However, basketball instruction in schools still tends to emphasize technical training, while psychological aspects, particularly concentration, receive limited attention. This study aimed to examine the effect of concentration-based training using the Grid Concentration Test (GCT) on students' free throw accuracy. A quantitative approach with a quasi-experimental design employing a pretest-posttest control group was used. The study involved 66 eighth-grade students from an Islamic junior high school, who were assigned to an experimental group and a control group through cluster random sampling. Data were collected using a standardized free throw shooting accuracy test. Statistical analyses included descriptive statistics, the Shapiro–Wilk normality test, Levene's homogeneity test, and the Mann–Whitney U test because the data were not normally distributed. The findings revealed that both groups had comparable initial abilities before the intervention. Following the training program, students who participated in concentration-based training demonstrated better free throw shooting accuracy than those who received conventional practice. These findings indicate that concentration training helps students maintain focus, improve movement coordination, and perform more accurate and consistent free throws. Furthermore, this study demonstrates that the Grid Concentration Test (GCT) can be utilized not only as an instrument for assessing concentration but also as a practical training medium to support sports skill development. Therefore, GCT can serve as an alternative instructional strategy that integrates psychological and technical aspects to enhance free throw shooting performance in basketball learning.